1990
DOI: 10.1002/jmor.1052050107
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of sperm development and mature sperm morphology in three species of commensal bivalves (Mollusca: Galeommatoidea)

Abstract: Ultrastructural features of the ovotestes, spermatogenesis, and the mature sperm are described for three galeommatid bivalves, Divariscintilla yoyo, Divariscintilla troglodytes, and Scintilla sp., from stomatopod burrows in eastern Florida. All three species yielded similar results except with respect to mature sperm dimensions. The ovotestis contains three types of somatic cells within the testicular portion: flattened myoepithelial cells defining the outer acinal wall; underlying pleomorphic follicle cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 32 publications
5
60
0
5
Order By: Relevance
“…Hodgson & Burke 1988); Spondylus sinensis based on S. nicoharicus ; Limaria hians based on L. fragilis ; Atrina pectinata based on A. vexillum ; Neotrigonia bednalli (Healy 1989); Neotrigonia margaritacea (Healy 1996b); Psilunio littoralis based on Velesunio ambiguus (Healy 1989); Cardita calyculata based on Cardita muricata (Healy 199Sb); Astarte castanea coded based on crassatellids2 Eucrassatella cumingii, E. kingicola, and Talabrica aurora (Healy 1995b); Galeomma turtoni based on Divariscintilla yoyo, D. troglodytes, and Cintilla sp. (Eckelbarger et al 1990); Lasaea sp. based on L. subviridis (0 Foighil 1985a); Codakia orhicularis based on C. punctata (Healy 1995a); Chama gryphoides based on C. macerophylla (Hylander & 2This coding assumes monophyly of Crassatellidae + Astartidae, and that the sperm anatomy described for 3 crassatellids is the groundplan for the common ancestor of…”
Section: Sperm (Characters 154-169)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hodgson & Burke 1988); Spondylus sinensis based on S. nicoharicus ; Limaria hians based on L. fragilis ; Atrina pectinata based on A. vexillum ; Neotrigonia bednalli (Healy 1989); Neotrigonia margaritacea (Healy 1996b); Psilunio littoralis based on Velesunio ambiguus (Healy 1989); Cardita calyculata based on Cardita muricata (Healy 199Sb); Astarte castanea coded based on crassatellids2 Eucrassatella cumingii, E. kingicola, and Talabrica aurora (Healy 1995b); Galeomma turtoni based on Divariscintilla yoyo, D. troglodytes, and Cintilla sp. (Eckelbarger et al 1990); Lasaea sp. based on L. subviridis (0 Foighil 1985a); Codakia orhicularis based on C. punctata (Healy 1995a); Chama gryphoides based on C. macerophylla (Hylander & 2This coding assumes monophyly of Crassatellidae + Astartidae, and that the sperm anatomy described for 3 crassatellids is the groundplan for the common ancestor of…”
Section: Sperm (Characters 154-169)mentioning
confidence: 99%
“…The temporary acrosorne has not been observed in any non-anomalodesmatan bivalve. Anterior act-osomal vesicle: (0) (0 Foighil 1985a,b;Eckelbarger et al 1990). Anterior nuclear fossa: a/p (Healy 1990).…”
mentioning
confidence: 99%
“…Nevertheless it was observed that the proacrosomal vesicles of N. Gharagozlou-Van Ginneken & Pochon-Masson, 1971;Popham, 1979;Franz6n, 1983;Healy, 1989Healy, , 1995Eckelbarger et al, 1990;Hodgson et al, 1990), that is, composed of round mitochondria surrounding a pair of orthogonally arranged centrioles (an arrangement characteristic of aquasperm in general; cf. Jamieson, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…All other bivalves possess a single, conical acrosomal vesicle, although during sperrnatogenesis in most of these species, multiple proacrosomal vesicles (which fuse to form the definitive acrosomal vesicle) are produced by the Golgi complex (see Longo & Dornfeld, 1967;Longo & Anderson,1969;Popham, 1979;Franz6n, 1983;Healy, 1989Healy, , 1995Hodgson & Bernard, 1986;Eckelbarger et al, 1990;Hodgson et al, 1990). The morphology of the mature acrosome of unionoids has been studied by various workers but with differing interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Utrastructural studies have been described the spermatogenesis and spermatozoa of a number of bivalve species using electron microscopy (Longo and Dornfelds, 1967;Longo and Anderson, 1969;Popham, 1979;Bernard and Hodgson, 1985;Hodgson and Bernard, 1986;Healy, 1989;Eckelbarger et al, 1990;Eckelbarger and Davis, 1996;Gaulejac et al, 1995;Chung and Ryou, 2000;Chung et al, 2007Chung et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%